Værk, offentlighed, (net)arkiv. Transformationen af det litterære felt i medialiseringens tidsalder og hvordan vi sikrer det for eftertiden - Kromann, Thomas Hvid (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2017)
Thomas Hvid Kromann: The literary work, the public sphere, (net)archive – transformation of the literary field in the mediatisation age and how we save it for posterity The article examines the ongoing transformation of the Danish literary field: what consequences does technological development in particular have for the concept of the literary work, the (literary) public sphere and for the possibilities for storing digital platforms that house both literary works, which are not associated with the printed media, and discussion forums on the internet? The author Caspar Eric’s publications are used as a case for a contemporary expansion of the concept of the literary work, since Eric’s work is not limited to the printed media, but also includes writing experiments, which he publishes on digital platforms in parallel with the official printed versions. The article argues that Eric’s publications in an extended literary field, indicate a need for a thorough reassessment of our delimitations of a literary work. Connected to the expansion of the public sphere, one finds a levelling of literary criticism, partly connected to the rise of social media. Based on the now closed sites Litlive and Promenaden the limits and possibilities of this tendency are examined. Finally, the article discusses the existing conditions for archiving these sites in order to save them for posterity, and it is reasoned that literary research within contemporary literature, beneficially, should include the archiving of literary source material.